Studying the effect of changing the thickness of the layers of the perovskite solar cell (ZnTe /CH3NH3PbI3 /TiO2/ZnO/FTO) using the simulation program (SCAPS 1-D) - Raddad Mahmoud; raad rasool (College of Education for Pure Sciences, 2022)
This research includes a study of the effect of the thickness of each layer of perovskite solar cell (CH3NH3PbI3) /TiO2/ZnO/FTO) and selecting the best thickness to obtain the highest efficiency of the cell, and studying the effect of adding a back surfsce layer on the efficiency of the solar cell using (SCAPS1-D). The perovskite (CH3NH3PbI3) was adopted as absorption layer and its  thickness tested from (1-7µm) with an increase of (1µm) to obtain the best thickness for best efficiency of the solar cell, its best thickness was (5µm), the thickness of the buffer layer (TiO2) was tested from (0.5-1.5 µm) with an increase of (0.25µm) and its best thickness was (0.5 µm), the thickness of the transparent conduction oxide (FTO) layer was tested (0.1-1.1µm) with an increase of (0.2µm) and its best thickness was (0.1 µm) and the thickness of the window layer(ZnO) was tested (0.1-0.5 µm) with an increase of (0.1µm) and its best thickness was (0.1µm).The effect of the window layer on the thickness of the buffer layer was studied and it was found that the best thickness of the buffer layer is (0.05µm). Finally, a back surface field layer was added, which is zinc telluride (ZnTe) with a thickness of (0.1 µm) and its thickness was studied, and its best thickness was (0.05µm) .It was found that the best thickness of the absorbent layer after adding the back surface field layer is (1µm). The final outputs of the cell were as follows: Voc=1.288(V), Jsc=25mA/cm2, FF=89.55%, ƞ=28.82%